DEIKSIS DALAM FILM THE BOSS BABY KARYA TOM MCGRATH: SUATU ANALISIS PRAGMATIK - WENUR, FERGY J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACTS Â Â ThisÂ researchÂ â€œ DeiksisÂ dalamÂ Film The BossÂ BabyÂ karyaÂ TomÂ McGrathâ€.Â ThereÂ areÂ 5Â typesÂ ofÂ deixis,Â those are:Â personÂ deixisÂ (firstÂ person,Â secondÂ person,Â andÂ thirdÂ person),Â placeÂ deixis,Â timeÂ deixis,Â discourseÂ deixis,Â andÂ socialÂ deixis.Â DeixisÂ belongsÂ toÂ pragmaticsÂ theÂ wordÂ deixisÂ comeÂ fromÂ theÂ GreekÂ deiktikos,Â itâ€ŸsÂ means,Â â€žpointingâ€Ÿ. Â TheÂ objectiveÂ ofÂ thisÂ researchÂ areÂ toÂ identifyÂ andÂ classifyÂ theÂ typesÂ ofÂ deixisÂ andÂ toÂ analyzeÂ theÂ usageÂ ofÂ deixisÂ inÂ theÂ filmÂ TheÂ BossÂ BabyÂ byÂ TomÂ McGrath.Â TheÂ methodÂ usedÂ inÂ thisÂ researchÂ isÂ descriptiveÂ method.Â TheÂ dataÂ areÂ identified,Â classifiedÂ andÂ analyzedÂ descriptively.Â TheÂ dataÂ wereÂ analyzedÂ basedÂ onÂ LevinsonÂ theory. Â TheÂ resultÂ showsÂ thatÂ thereÂ areÂ fiveÂ typesÂ ofÂ deixisÂ inÂ theÂ filmÂ TheÂ BossÂ Baby,Â thoseÂ areÂ personÂ (firstÂ person: I,Â me,Â our,Â we,Â andÂ my;Â secondÂ person: yourÂ andÂ you;Â thirdÂ person:Â he,Â him,Â they,Â andÂ them),Â placeÂ deixis:Â here,Â house,Â overÂ hereÂ andÂ where,Â timeÂ deixis:Â time,Â Monday,Â 07.00Â A.M,Â now,Â weeks,Â ever,Â faster,Â yearsÂ ago,Â days,Â Friday,Â andÂ longÂ timeÂ ago,Â discourseÂ deixis:Â this,Â that,Â andÂ this,Â andÂ socialÂ deixis:Â brother,Â maâ€Ÿam,Â mom,Â dad,Â sir,Â bigÂ bossÂ baby,Â mr.Â ladyÂ man,Â boss,Â andÂ ladies,Â whearesÂ theÂ usageÂ ofÂ deixisÂ foundÂ inÂ theÂ filmÂ areÂ symbolÂ andÂ gesturalÂ usage. Â ItÂ isÂ expectedÂ thatÂ thisÂ researchÂ willÂ helpÂ theÂ studentsÂ andÂ theÂ otherÂ readersÂ toÂ learnÂ theÂ pragmaticsÂ aspects,Â especiallyÂ aboutÂ deixis. Keywords:Â Film,Â Pragmatics,Â Deixis.